Comparing Cost, Efficacy, and Safety of Intravenous and Topical Tranexamic Acid in Total Hip and Knee Arthroplasty - DiBlasi, Joseph F. (Am J Orthop (Belle Mead NJ), 2016)
We conducted a study to compare the cost, efficacy, and safety of intravenous (IV) tranexamic acid (TXA) and topical TXA in primary total hip arthroplasty (THA) and total knee arthroplasty (TKA). We retrospectively reviewed the cases of 291 patients who received either IV TXA or topical TXA before and after surgery. Significant differences favored topical TXA in reducing the postoperative decrease in hemoglobin levels in THA (P = .031) and TKA (P = .015) and calculated blood loss in TKA (P = .019). The groups did not differ in transfusion requirements for either THA or TKA. Topical TXA cost significantly more than IV TXA (P ≤ .0001). The benefits of using topical TXA to reduce the perioperative decrease in hemoglobin levels come with increased cost.